Effects of immediate‐release opioid on memory functioning: a randomized‐controlled study in patients receiving sustained‐release opioids. (3rd April 2014) - Kamboj, S.K.; Conroy, L.; Tookman, A.; Carroll, E.; Jones, L.; Curran, H.V.
Abstract Background The effects of opioid medication on cognitive functioning in patients with cancer and non‐cancer pain remain unclear. Method In this mechanistic randomized, double‐blind, placebo‐controlled, cross‐over study of patients (n = 20) receiving sustained‐release and immediate‐release opioid medication as part of their palliative care, we examine memory effects of an additional dose of participants' immediate‐release medication (oxycodone or morphine) or placebo. Immediate prose recall and recall of related and unrelated word pairs was assessed pre‐and post‐drug (placebo or immediate‐release opioid). Memory for these stimuli was also tested after a delay on each testing occasion. Finally, performance on an 'interference' word pair task was assessed on the two testing occasions since proactive interference has been posited as a mechanism for acute opioid‐induced memory impairment. Result Unlike previous work, we found no evidence of memory impairment for material presented before or after individually tailored, 'breakthrough' doses of immediate‐release opioid. Furthermore, immediate‐release opioid did not result in increased memory interference. On the other hand, we found enhanced performance on the interference word pair task after immediate‐release opioid, possibly indicating lower levels of interference. Conclusion These results suggest that carefully titrated immediate‐release doses of opioid drugs may not cause extensive memory impairment as previously reported, and in fact, may improve memory in certain circumstances. Importantly, our findings contrast strikingly with those of a study using the same robust design that showed significant memory impairment. We propose that factors, such as depressive symptoms, education level and sustained‐release opioid levels may influence whether impairment is observed following immediate‐release opioid treatment.